Costantino Dardi - Paesaggi platonici - Pivetta, Michelangelo (Firenze Architettura, 2017)
Along the corridor that eels the East part of Veneto, crossing that endless plain after Venice, where once the fields and poplars rows mark the territory and today small industries and shopping centers poison it, it is normal to ask after years of habit what could be that dense cube-shaped spatial structure that is unstable on the edges of a normal gasoline pump shelter. That's Costantino Dardi.